PENGARUH PERUBAHAN BUDAYA ORGANISASI KARAKTERISTIK INDIVIDU DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PT. RAMAYANA LESTARI SENTOSA,TBK SAMARINDA SQUARE - Maya Ria Astuti (OBOR: Oikonomia Borneo, 2020)
The purpose of this study was to determine the effect of changes in organizational culture, individual characteristics and leadership on job satisfaction of employees of PT. Ramayana Lestari Sentosa, Tbk Samarinda Square. This research method is quantitative with data collection using quota sampling techniques with a total of 48 samples, data collection techniques using descriptive analysis, the data presented is data obtained from the results of respondents' answers using the SPSS version 2.2 calculation tool to fully understand the relationship between each variable. . From the results of the t-test analysis (partial) there is a significant effect of 10% which is relatively low or there is no influence on the variables of organizational culture change (X1) Individual Characteristics (X2) and Leadership (X3) on employee job satisfaction (Y) at PT . Ramayana Lestari Sentosa, Tbk Samarinda Square. And while the rest is 90% which may be influenced by other factors that are not explained by the researcher in this thesis. But from the results of the F test (simultaneous) the three variables have no influence on the variables of organizational culture change (X1) Individual Characteristics (X2) and leadership (X3) on employee job satisfaction at PT. Ramayana Lestari Sentosa, Tbk Samarinda Square.